Quality and fatty Acid Composition of Coconut Oil in Relation to Varietal variation and Mineral Nutrition - V S Geetha Kumari (Department of Soil Science and Agricultural Chemistry, College of Agriculture, 1994)
Coconut is a perennial oil seed crop with a large number of cultivars having widely varying growth and yield characteristics. It is both an agricultural and industrial crop with immense economic importance. A variety of edible oils are available in the market today with wide variations in quality parameters and nutritional characteristics. Although product quality is influenced by many factors associated with production, harvesting, curing and processing; quality is influenced to a greater extent by the genetic parameters and chemical composition. Assessment of quality parameters and fixing standards for the nutritional aspects are to be considered with top priority for the development of new varieties/cultivars along with the yield attributes. Considering the afore mentioned facts in view, it was felt essential to study the effect of varietal variation and mineral nutrition on the oil content, quality and fatty acid composition of coconut oil. Nuts collected from different varieties/cultivars from RARS, Pilicode, Instructional farm, Vellayani and palms of an ongoing fertilizer trial of the CRS, Balaramapuram, were subjected to chemical analysis to study the above aspects. The results of the analysis were summarised and appropriate conclusions drawn. The effect of varietal variation on the oil content and quality parameters like acid value, saponification value and iodine value were found to be significant. Minor quality parameters like Reichert – Meissel and Polenske value also showed considerable differences among the varieties. The fatty acid composition of oil from selected varieties also had shown considerable variation. The effect of mineral nutrition on the oil quality and fatty acid composition of coconut oil were found to be insignificant. The oil content was not influenced by nitrogen and phosphorus while potassium had a significant but negative effect on oil content. The influence of N, P and K fertilizers on the quality parameters like acid value, saponification value and iodine value was not significant in general. Minor quality parameters like Reichert – Meissel and Polenske value showed variation due to fertilizer treatments. The fatty acid composition of oil from selected treatments. The fatty acid composition of oil from selected treatments were also influenced by mineral nutrition. From the results of the study it can be concluded that quality parameters of coconut are much influenced by varietal differences than by mineral nutrition. Thus it is evident from the study that the genetic variability has got a greater role to play in modifying quantity parameters and chemical composition of the most important tropical adible oil namely coconut oil. Selection and breeding should be directed towards tailoring new varieties with higher oil content, quality indices and fatty acid composition.